Air‐Stable Oxyallyl Patterns and a Switchable N‐Heterocyclic Carbene. Issue 28 (11th May 2020) - Tomás‐Mendivil, Eder; Devillard, Marc; Regnier, Vianney; Pecaut, Jacques; Martin, David
Abstract: Oxyallyl derivatives are typically elusive compounds. Even recently reported "stabilized" 1, 3‐diaminooxyallyl species are still highly reactive and have short lifetimes at room temperature. Herein, we report the synthesis and preliminary study of mesoionic pyrimidine derivatives that feature 1, 3‐bis(dimethylamino)oxyallyl patterns with an unprecedented level of stabilization. The latter are not only insensitive towards air and moisture, but they are also compatible with the formation of an ancillary stable N‐heterocyclic carbene moiety. As the oxyallyl pattern is proton‐responsive, it allows the reversible switching of the electronic properties of the carbene, as a ligand. Abstract : Hand in hand : The 1, 3‐diaminooxyallyl pattern, usually short‐lived at room temperature, becomes air‐ and moisture‐stable when associated with amidinium derivatives. It can even co‐exist with an N‐heterocyclic carbene moiety. In turn, the electronic properties of the carbene ligand can be switched by protonation/deprotonation at the oxygen atom of the oxyallyl moiety.